Modulation of the Heteromeric Kir4.1-Kir5.1 Channel by Multiple Neurotransmitters via G(αq)-coupled Receptors - Rojas, Asheebo (2008)
The heteromeric Kir4.1-Kir5.1 channel is a candidate sensing molecule for CO(2) central chemoreception. Since it is known that the CO(2) central chemoreception is subject to neural modulations, we performed studies to test the hypothesis that the Kir4.1-Kir5.1 channel is modulated by neurotransmitters critical for respiratory control, including serotonin (5-HT), substance-P (SP), and thyrotropin releasing hormone (TRH). Immunocytochemistry showed coexpression of Kir4.1 and Kir5.1 in cultured brainstem neurons. The heteromeric Kir4.1-Kir5.1 channel was strongly inhibited by SP, TRH, and 5-HT when expressed in Xenopus oocytes. Such inhibitions were not seen in the homomeric Kir4.1 channel. The inhibition was specific and had clear dose dependence. The effect relied on activation of G-proteins and protein kinase C (PKC), a downstream second messenger of G(αq) coupled receptors. The neural modulation did not compromise the channel sensitivity to CO(2)/pH, as the channel remained to be inhibited by acidic pH with a pre-exposure to the neurotransmitters. Firing rate of cultured brainstem neurons in microelectrode arrays was augmented by application of SP or DOI to the culture medium. The augmentation of the firing rate was blocked by PKC inhibitors suggesting that PKC underscored the inhibitory effect in brainstem neurons as well. These results therefore indicate that the Kir4.1-Kir5.1 channel is modulated by neurotransmitters critical for respiratory control, and the neural modulation appears to enhance channel sensitivity to high PCO(2) and acidic pH.